NZ J Ecol 2017
DOI: 10.20417/nzjecol.41.11
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of horizontal versus vertical camera placement to detect feral cats and mustelids

Abstract: Invasive predators are a threat to biodiversity in New Zealand. However, they are often difficult to monitor because of the animals' cryptic, mobile behaviour and low densities. Camera traps are increasingly being used to monitor wildlife, but until recently have been used mainly for large species. We aimed to determine the optimal camera alignment (horizontal or vertical) for detecting feral cats (Felis catus) and mustelids (Mustela furo, M. erminea and M. nivalis). We deployed 20 pairs of cameras, each pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…In addition to the three mammals commonly targeted with tracking tunnels, remote cameras also recorded more possums and seven other species that tracking tunnels missed completely, including other introduced mammals (especially cats) and native birds. The number of species that could be recorded by remote cameras may be even larger considering that cameras can remain active over much longer periods of time than tunnels without additional effort in the field (Nichols et al 2017). Longer monitoring periods also enable remote cameras to detect animals at low densities (Rowcliffe et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the three mammals commonly targeted with tracking tunnels, remote cameras also recorded more possums and seven other species that tracking tunnels missed completely, including other introduced mammals (especially cats) and native birds. The number of species that could be recorded by remote cameras may be even larger considering that cameras can remain active over much longer periods of time than tunnels without additional effort in the field (Nichols et al 2017). Longer monitoring periods also enable remote cameras to detect animals at low densities (Rowcliffe et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Magle et al 2014;Allen et al 2016a, b). To efficiently monitor mammals using remote cameras, appropriate deployment of the cameras is crucial (Nichols et al 2017). Previous research has suggested that animal detection rates from cameras differ based on the methodology (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trail cameras are being used increasingly to monitor small mammals in New Zealand (Nichols et al 2017;Anton et al 2018;Murphy et al 2018;Nugent et al 2019). Cameras monitor a broad range of species and can provide information on species identity (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is often wide variation in the deployment of camera traps within a landscape (i.e., number of sampling units used at each site and their distance from each other) [18,19]. For example, camera traps may be placed in a variety of ways, such as with a horizontal or vertical orientation [20,21]; baited or unbaited [22,23]; non-biased or biased allocation across a landscape [24], as in systematic grids/transects [9,25,26]; or deliberately placed near likely target species ‘hot spots’, such as trails, roads, and water features [27].…”
Section: Introductionmentioning
confidence: 99%